Bidirectional structural priming across alternations: evidence from the generation of dative and benefactive alternation structures in German - Pappert, Sandra; Pechmann, Thomas (Language, cognition and neuroscience, 2013)
In two experiments, we investigated the primed generation of dative and benefactive alternation structures in German. As benefactive alternation structures differ from dative alternation structures in event semantics but are assumed to inherit some of their syntactic properties, the crucial question here is whether bidirectional cross-alternation priming can be found. Experiment 1 revealed priming of dative alternation structures by benefactive alternation structures whereas Experiment 2 is the first to our knowledge to show priming of benefactive alternation structures by dative alternation structures. We conclude that structural persistence neither hinges on lexical subcategorisation frames nor is it necessarily sensitive to semantic and syntactic differences associated with dative and benefactive alternation structures. However, the effects we found are compatible with both a phrase structural account and a proto-roles account of structural priming. Moreover, the new sentence generation paradigm we designed qualified as an appropriate method to investigate structural priming for nondepictable events.
Online veröffentlicht: 06. August 2012
Gesehen am 23.08.2024